Modification of the Pseudomonas aeruginosa toxin 2‐heptyl‐1‐hydroxyquinolin‐4(1H)‐one and other secondary metabolites by methyltransferases from mycobacteria. (8th November 2020) - Sartor, Pascal; Bock, Jonathan; Hennecke, Ulrich; Thierbach, Sven; Fetzner, Susanne
Abstract : The opportunistic pathogen Pseudomonas aeruginosa, one of the most prevalent species in infections of the cystic fibrosis lung, produces a range of secondary metabolites, among them the respiratory toxin 2‐heptyl‐1‐hydroxyquinolin‐4(1 H )‐one (2‐heptyl‐4‐hydroxyquinoline N ‐oxide, HQNO). Cultures of the emerging cystic fibrosis pathogen Mycobacteroides abscessus detoxify HQNO by methylating the N ‐hydroxy moiety. In this study, the class I methyltransferase MAB_2834c and its orthologue from Mycobacterium tuberculosis, Rv0560c, were identified as HQNO O ‐methyltransferases. The P. aeruginosa exoproducts 4‐hydroxyquinolin‐2(1 H )‐one (DHQ), 2‐heptylquinolin‐4(1 H )‐one (HHQ), and 2‐heptyl‐3‐hydroxyquinolin‐4(1 H )‐one (the ' Pseudomonas quinolone signal', PQS), some structurally related (iso)quinolones, and the flavonol quercetin were also methylated; however, HQNO was by far the preferred substrate. Both enzymes converted a benzimidazole[1, 2‐ a ]pyridine‐4‐carbonitrile‐based compound, representing the scaffold of antimycobacterial substances, to an N ‐methylated derivative. We suggest that these promiscuous methyltransferases, newly termed as heterocyclic toxin methyltransferases (Htm), are involved in cellular response to chemical stress and possibly contribute to resistance of mycobacteria toward antimicrobial natural compounds as well as drugs. Thus, synthetic antimycobacterial agents may be designed to be unamenable to methyl transfer. Enzymes: S ‐adenosyl‐l ‐methionine:2‐heptyl‐1‐hydroxyquinolin‐4(1 H )‐one O ‐methyl‐transferase, EC 2.1.1.‐ Abstract : The MAB_2834c and Rv0560c proteins of Mycobacteroides abscessus and Mycobacterium tuberculosis were identified as small molecule methyltransferases with a broad specificity toward heteroaromatic substrates and O ‐ as well as N ‐methylation activity. 2‐Heptyl‐1‐hydroxyquinolin‐4(1 H )‐one, a respiratory inhibitor and major exoproduct of the opportunistic pathogen Pseudomonas aeruginosa, is a preferred substrate. The enzymes, termed heterocyclic toxin methyltransferases (Htm), likely contribute to resistance of mycobacteria toward antimicrobial compounds.